PENDEKATAN SOSIAL DALAM PENELITIAN HUKUM - Mulyani, Lilis (P2KK LIPI, 2010)
Recently, we are witnessing the vast expansion of the use of social methods in law research. The so-called socio-legal research is one way of using scientific methodologies in social science disciplines (such as sociology, anthropology, economics, language) to find answers for legal problems. In this paper I would like to unfold how these methods influence the legal reasoning in legal research, to what extent they can be used or even to be misused. Law, is a specific subject, in which law text are authoritative in nature, which makes it having its own particularities that differs it from other texts. As an authoritative text, approach to law is narrowed as it supposed to maintain the certainty of the law itself. However, legal problems do not always concern with merely legal text, it also touches many aspects of the societies, which for this part, law needs approaches from other social sciences methods. In this writing, legal research methods are differentiated based on the user of the information it will provide. Keywords: legal research, socio-legal studies, interdisciplinary studies